1968
DOI: 10.1126/science.162.3859.1279
|View full text |Cite
|
Sign up to set email alerts
|

Human Osteosarcomas: Immunologic Evidence Suggesting an Associated Infectious Agent

Abstract: Immunofluorescent studies have revealed a high incidence of antibodies to osteosarcomas in the serums of patients with this disease and their close associates which react with a common antigen (or antigens) in osteosarcomas. The distribution of these antibodies suggests the association of an infectious agent with this neoplasm which is capable of producing unrecognized infections in healthy contacts of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
2

Year Published

1970
1970
1981
1981

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(22 citation statements)
references
References 7 publications
2
17
1
2
Order By: Relevance
“…Hellstr6m, Hellstr6m, Bill, Pierce, and Yang described cell Received for publications 17 October 1973 and in revised form 4 November 1974. mediated-immunity to neuroblastoma in mothers of infants with that tumor (1). Morton and Malmgren demonstrated a high incidence of tumor-specific antibodies in family members of osteogenic sarcoma patients (2). This, in conjunction with their other studies, was interpreted as evidence for a possible viral etiology in some human cancers (3)(4)(5).…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…Hellstr6m, Hellstr6m, Bill, Pierce, and Yang described cell Received for publications 17 October 1973 and in revised form 4 November 1974. mediated-immunity to neuroblastoma in mothers of infants with that tumor (1). Morton and Malmgren demonstrated a high incidence of tumor-specific antibodies in family members of osteogenic sarcoma patients (2). This, in conjunction with their other studies, was interpreted as evidence for a possible viral etiology in some human cancers (3)(4)(5).…”
Section: Introductionmentioning
confidence: 50%
“…Morton and Malmgren reported that 80-90% of relatives of osteogenic sarcoma patients had antisarcoma antibodies as measured by immunofluorescence, and that 29% of the normal population also had this immunity (2). In a later report, Eilber and Morton also demonstrated antisarcoma immunity in 60-100% of relatives of patients with synovial cell sarcoma, rhabdomyosarcoma, or fibrosarcoma (4).…”
Section: The Assaymentioning
confidence: 86%
“…The cell membrane is the site of antigens associated with sarcoma (Morton et al 1969), and antibodies against tumour cells have been demonstrated in osteosarcoma patients. Treated osteosarcoma patients showing no symptoms of disease for several years carry high levels of cytotoxic antibodies against the neoplasm (Morton & Malmgren 1968). The cytotoxic antibody levels were found to be inversely correlated with the presence of tumour.…”
Section: Discussionmentioning
confidence: 86%
“…He had no history of contact with breast-cancer patients. In this context, a number of investigators (Burger et al, 1977;G-raham-Pole et al, 1976;Byers et al, 1975;Morton & Malmgren, 1968) have reported that close family contacts of cancer patients may be sensitized to the cancer since they react in in vitro assays that measure antitumour immunity. Although extensive family studies were not undertaken, no positive responses were recorded in the 10 families tested.…”
Section: Discussionmentioning
confidence: 99%